Analysis of User Experience and Patient Perceptions of an Artificial Intelligence (AI) Application for Diabetes Management: A Qualitative Study - Yudha, Nyoman Satvika Dharma; Pratama, Mirza Zaka; Fajarpeni, Prisca Anindhita (Universitas Brawijaya, 2026)
Background: Diabetes mellitus is a chronic condition requiring significant long-term self-management. Artificial Intelligence (AI) technology offers novel potential to support patients in their daily self-care routines. However, patient perceptions and real-world user experiences with these AI applications, particularly in low- and middle-income settings, remain understudied. Objective: To explore the user experience and perceptions of patients with diabetes and their caregivers using Inadia, a WhatsApp-based AI application designed for diabetes management in Indonesia. Methods: This study employed a descriptive qualitative design. Semi-structured in-depth interviews were conducted with six participants (patients with diabetes and caregivers) who were users of the Inadia application. Data were analyzed using the six-phase thematic analysis framework developed by Braun & Clarke. Ethical approval was obtained from an institutional review board, and all participants provided written informed consent. Results: Five major themes emerged from the analysis: (1) Usability and accessibility through the familiar WhatsApp interface; (2) The functional value and positive clinical–psychological impact of the application; (3) The critical influence of AI communication style and its perceived emotional sensitivity; (4) Technical challenges, primarily server delays, and user cost concerns; and (5) User-specific needs and expectations for future development. Conclusion: The Inadia application demonstrates significant promise in supporting diabetes self-management, largely due to its high accessibility via WhatsApp. However, its sustained success and long-term user adoption are critically dependent on resolving technical stability issues and, crucially, refining the AI’s communication style to be more emotionally supportive and encouraging.